Comunidade tradicional dos “Areais da Ribanceira”, Imbituba (State of Santa Catarina): development, territoriality and construction of rights - Mombelli, Raquel (FCL-UNESP Laboratório Editorial, 2013)
The article analyses the trajectory of the search for the cultural recognition and rural land regularization of common use properties, exploited for more than one century, by the social group self-entitled as “Comunidade Tradicional dos Areiais da Ribanceira”, in the city of Imbituda, within a context of acceleration of the denominated large development projects. It shows that, despite the rights of the “Comunidades Tradicionais” assured by the Federal Constitution of 1988 and international legal dispositives, those communities are systemically ignored upon the “myth of the progress”. This social group is seen as a hindrance to the projects and target for the right restriction policies by the Brazilian State. It evidences how the privatization of lands in common use led to the de-territorialization of the community and how this fact threatens the reproduction of accumulated traditional acknowledges, the free access to natural resources and the environmental action of these collective subjects, which allowed the preservation of an important regional system of sandbar.